Reclaiming authorship : literary women in America, 1850-1900 - Williams, Susan S. (University of Pennsylvania Press, 2006)
"Reclaiming Authorship augments our knowledge of the female literary tradition and enriches our grasp of the process by which women authors sought public status in a publishing marketplace. It challenges basic tenets of the origins of realism and posits a definable historical transition from the romantic to the realist."--Cecelia Tichi.